Long-Term Therapy With Wu-Ling-San, a Popular Antilithic Chinese Herbal Formula, Did Not Prevent Subsequent Stone Surgery - San-Yuan Wu MD, PhD; Huey-Yi Chen MD, PhD; Kao-Sung Tsai MD, PhD; Jen-Huai Chiang MS; Chih-Hsin Muo MS; Fung-Chang Sung PhD; Yung-Hsiang Chen PhD; Wen-Chi Chen MD, PhD (SAGE Publishing, 2016)
Traditional Chinese herbal medicine (CHM), which is widely used to treat pain and urolithiasis, is a promising therapy for urinary stone prevention. This study investigated the clinical efficacy of a popular CHM, Wu-Ling-San (WLS), in Taiwan for the prophylaxis of recurrent nephrolithiasis as assessed by surgical stone treatment via a nationwide population-based cohort study. The National Health Insurance Research Database, 2000-2010, which included one million patient records. All patients diagnosed with stone disease at the beginning of the study. The matched controls (4-fold the number of WLS patients) were stone patients who did not take WLS. Data analysis included the stone surgeries following the first treatment. We enrolled 11 900 patients with stone disease, and the incidence of stone patients in this database was 1.19%. The prevalence of comorbidities such as benign prostate hyperplasia, chronic kidney disease, diabetes mellitus, and urinary tract infection, but not hypertension, was significantly higher in WLS users. Several patients in both groups were prescribed potassium citrate. The stone treatment rate was significantly higher in WLS users (17.85%) than in the non-WLS users (14.47%). WLS users with an associated comorbidity had a higher treatment rate than the non-WLS users: 21.05% versus 16.70%, respectively. The surgery rate for upper urinary tract stones was higher in WLS users than in the non-WLS users (adjusted hazard ratio, 1.28; 95% confidence interval, 1.08-1.52; P < .05). The stone treatment rate (52.79%) was significantly higher in patients who used a very high amount of WLS (adjusted hazard ratio, 3.02; 95% confidence interval, 2.30-3.98). Stone patients using a high amount of WLS use had a high stone surgical rate. Long-term therapy with WLS did not have a preventive effect on stone surgical treatment. Long-term potassium citrate therapy as a preventive measure appeared to be underutilized in this study.